Element Levels in Feathers of Atlantic Puffins (Fratercula arctica) in Iceland: Establishing Background Levels in an Arctic Migratory Species - Joanna Burger; Erpur Snær Hansen; Kelly Ng; Michael Gochfeld (Toxics)
Examining contaminant concentrations in birds in Arctic environments is important for managing species for assessing long-term trends. Recent reports on mercury (Hg) concentrations in Arctic species of seabirds has identified a need for data from missing regions or species. We measured arsenic (As), cadmium (Cd), chromium (Cr), lead (Pb), manganese (Mn), Hg and selenium (Se) in the body feathers of Atlantic Puffin (Fratercula arctica) from four colonies in Iceland in 2011 and one in 2009. Puffins forage on small fish at an intermediate trophic concentration. We found that (1) concentrations examined in the colony in 2009 were lower than in 2011 for all metals except As and Hg, and (2) concentrations of Cd and Se varied significantly among colonies for feathers collected in 2011. Pb concentrations in Puffin feathers in one colony were 14-fold higher in 2009 than in 2011 (mean of 805 ng.g−1 vs. 58 ng.g−1). The highest mean Hg concentration in 2011 was 362 ng.g−1 and was 4880 ng.g−1 for Se. The concentrations of Hg in the Atlantic Puffins reported in this study were similar to, or lower than those reported for the same species elsewhere and for Tufted Puffin from the Pacific.